Disseminated Chickenpox Following Live Varicella Vaccination in a Crohn’s Disease Patient on Combination Immunosuppression - Quintin Solano; Sarah Uttal; Peter D. R. Higgins; Jeffrey A. Berinstein (Case Reports in Gastrointestinal Medicine)
Novel therapeutics used in the treatment of inflammatory bowel disease pose an increased risk of viral reactivation in patients. We present a case of a patient with refractory Crohn’s disease (CD) who developed primary varicella (chickenpox) of a vaccine-viral strain after receiving combination immunosuppression with high-dose corticosteroids, tumor necrosis factor inhibitor (TNFi), and a Janus kinase inhibitor (JAKi) in the hospital. While this patient recovered and did not experience long term adverse effects, her case provides an opportunity for improvement. To improve safety, healthcare facilities should develop protocols that use electronic medical records enhanced with clinical decision support systems to identify and protect immunocompromised patients from inappropriate live vaccinations.